(untitled) (Bangladesh Journal of Pharmacology, 2018)
The aim of this systematic review is to evaluate the effects of cotoneaster manna on neonatal jaundice. The studies were selected from 1980 to 2017 using the main databases. Eight clinical trials with a total of 862 infants were selected from the 116 primary studies. All these trials had at least two groups for which the studied outcomes were measured before the intervention and at 12, 24, 36 and 48 hours after intervention. Generally, the meta-regression analysis showed a direct insigniﬁcant relationship between the baseline bilirubin level in the infants before the intervention and the estimated results. Although the findings confirm the effectiveness of cotoneaster manna products in the treatment of neonatal jaundice compared to the standard interventions or treatments (phototherapy), further clinical trials are strongly recommended, especially with larger sample sizes, more extensive geogra-phical areas, and a variety of subjects in different parts of the world.